The Effect of Obesity on the Presence of Sebaceous Cysts and Some Hematological Variables - Reem khalid Ibrahim; Mohammed S. Hussein; Shahd Hussein Rzaig (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background High triglycerides may lead to other conditions such as hypothyroidism or liver and kidneydisease. Certain medications, such as beta-blockers, birth control pills and steroids, can increase triglyceridelevels. Other factors can affect triglyceride levels Methodology Biochemical tests included (serumcholesterol, triglyceride, LDL, RBS and HbA1c These tests were performed according to the workingmethod of each analysis on the device Full automate and TUSO Hematological test included( WBC countRBC count Hb and PCV) These tests were conducted at CBC device .Result illustrates a study of some biochemical variables for people with lipoma and comparing them withhealthy peoples , where mean of the affected persons for cholesterol and triglyceride tests was 312, 296,respectively, compared with the control 116, 89, respectively, and the level of sugar and HbA1c in theaffected persons was 11, 226 on Respectively compared to control 86, 3, respectively, and this explains thatthere is a direct relationship between the rise in fat and blood sugar with the emergence of lipomaConclusion We conclude that the most vulnerable people are those who suffer from high levels of triglyceridesand cholesterol, as well as those with high blood sugar, as well as the genetic factor that plays a major rolein causing this disease, as the genetic factor gave a large percentage of infection with this disease, as well asthe quality of nutrition has a great role